Moderasi Beragama dalam Keragaman pada Perguruan Tinggi Umum di Era Society 5.0: Strategi dan Implementasi - Ramadhan, Mochammad Rizal (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2022)
This study aims to discuss the strategy and implementation of religious moderation in diversity in the era of society 5.0. This study uses a qualitative approach and data processing using a descriptive-analytical method. The results and discussion of this study indicate that there are several strategies used in implementing the concept of religious moderation in public universities that have diversity. This study concludes that religious moderation in diversity in public universities requires certain strategies in its implementation in the era of society 5.0 which is full of challenges. Important efforts in implementing religious moderation today are aimed at creating a generation that is moderate and not easily influenced by radical ideas, as well as strengthening tolerance among religious believers.